Research of eMBMS's Security Mechanism and Content Protection - Yi Zhou; Jia Liu; Minrui Shi (Dianxin kexue)
Through the research of 3GPP's eMBMS security mechanism and being combined with the characteristics of operators, the influence of current network by the deployment of eMBMS security mechanism was given. On the basis of the research above, a proposal was made for how the operator deploys eMBMS security mechanism.